2023
DOI: 10.3389/fimmu.2023.1092801
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Helicobacter pylori-derived VacA attenuates allergic airway disease

Abstract: BackgroundAsthma is an incurable heterogeneous disease with variations in clinical and underlying immunological phenotype. New approaches could help to support existing therapy concepts. Neonatal infection of mice with Helicobacter pylori or administration of H. pylori-derived extracts or molecules after birth have been shown to prevent the development of allergic airway disease later in life. This study evaluated the potential therapeutic efficacy of H. pylori vacuolating cytotoxin A (VacA) in allergic airway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Gastric H. pylori colonization was associated with a shift in the composition of microbial communities in the lung and oral cavity; future studies would be needed to determine if an altered microbiome persists as H. pylori infected animals mature into adulthood. The therapeutic value of H. pyloriderived components for reducing allergic airways inflammation is under investigation; given our present findings it may be of interest to assess whether altering the lung microbiome during infancy could prevent development of childhood asthma 64,65 .…”
Section: Discussionmentioning
confidence: 93%
“…Gastric H. pylori colonization was associated with a shift in the composition of microbial communities in the lung and oral cavity; future studies would be needed to determine if an altered microbiome persists as H. pylori infected animals mature into adulthood. The therapeutic value of H. pyloriderived components for reducing allergic airways inflammation is under investigation; given our present findings it may be of interest to assess whether altering the lung microbiome during infancy could prevent development of childhood asthma 64,65 .…”
Section: Discussionmentioning
confidence: 93%
“…Gastric H. pylori colonization was associated with a shift in the composition of microbial communities in the lung and oral cavity; future studies would be needed to determine if an altered microbiome persists as H. pylori infected animals mature into adulthood. The therapeutic value of H. pylori -derived components for reducing allergic airways inflammation is under investigation; given our present findings it may be of interest to assess whether altering the lung microbiome during infancy could prevent development of childhood asthma [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of observational clinical studies have found that H. pylori infection is associated with a variety of chronic respiratory diseases 2,22 , especially with bronchial asthma 4,5 . At present, the risk effect of H. pylori infection on asthma is still controversial 23,24 , and some studies have suggested that H. pylori infection can increase the incidence and severity of asthma.…”
Section: Discussionmentioning
confidence: 99%